2013
DOI: 10.1016/j.ydbio.2013.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of rare and common variants determine complex diseases—Hirschsprung disease as a model

Abstract: Finding genes for complex diseases has been the goal of many genetic studies. Most of these studies have been successful by searching for genes and mutations in rare familial cases, by screening candidate genes and by performing genome wide association studies. However, only a small fraction of the total genetic risk for these complex genetic diseases can be explained by the identified mutations and associated genetic loci. In this review we focus on Hirschsprung disease (HSCR) as an example of a complex genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 109 publications
1
117
1
Order By: Relevance
“…Affected individuals lack enteric neurons along the gastrointestinal tract, leading to constipation or intestinal obstruction. The penetrance and severity of Hirschsprung's disease is often determined by interactions between genes within the GDNF/RET and EDNRB pathways, including an interaction between RET and NRG1 (Gabriel et al 2002;Garcia-Barcelo et al 2009;Wallace and Anderson 2011;Alves et al 2013). The key to success for these genetic studies lies in the important but limited genetic heterogeneity of each disorder.…”
Section: Insights From Mouse Modelsmentioning
confidence: 99%
“…Affected individuals lack enteric neurons along the gastrointestinal tract, leading to constipation or intestinal obstruction. The penetrance and severity of Hirschsprung's disease is often determined by interactions between genes within the GDNF/RET and EDNRB pathways, including an interaction between RET and NRG1 (Gabriel et al 2002;Garcia-Barcelo et al 2009;Wallace and Anderson 2011;Alves et al 2013). The key to success for these genetic studies lies in the important but limited genetic heterogeneity of each disorder.…”
Section: Insights From Mouse Modelsmentioning
confidence: 99%
“…Genetic studies have identified rare high-penetrance mutations in , cumulatively explaining only a modest number of cases (<10%) and often involving syndromic forms. 2,3 Surprisingly, significantly greater phenotypic variation is explained by two common low-penetrance non-coding variants at RET (rs2435357) 4 and NRG1 (MIM 142445) (rs4541858), 5 respectively. Of these, rs2435357 disrupts function of a GI-tract-specific enhancer in RET intron 1 through abrogation of SOX10 binding, thereby reducing RET expression.…”
Section: Introductionmentioning
confidence: 99%
“…HSCR is a multi-genetic condition with complex aetiology [5]. Mutations in RET proto-oncogene and endothelin receptor B (ENDRB) are the most frequent genetic insults [6].…”
Section: Introductionmentioning
confidence: 99%